Composites with improved microwave shielding properties

By using the complex of the use of thermoplastic resin and high -surface area of ​​carbon filler, the existing car radar sensor microwave shielding materials are heavy, expensive and complicated, and achieved a balanced effect between conductive and microwave absorption efficiency, effectively shielded effectively And absorb microwave radiation.

CN116171303BActive Publication Date: 2025-01-28SHPP GLOBAL TECH BV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202180064176.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-07-20
Filing Date
2021-07-20
Publication Date
2025-01-28
Estimated Expiration
2041-07-20

AI Technical Summary

Technical Problem

The microwave shielding materials of existing automotive radar sensors are heavy, expensive and complex in processing, and existing materials are difficult to balance conductivity and microwave absorption efficiency.

Method used

Use about 50%to 97%of thermoplastic resin (including polyester) and about 3%to 15%of carbon -based fillers. Carbon fillers have a main surface area of ​​500 to 1000m2/g. To measure their dielectric constants and dispersing losses within the frequency range of 120GHz.

Benefits of technology

A complex with dispersal losses between 5 and 30 and 0.5 to 45 can show at least 15%of the percentage of reflection power during the transmission mode at the frequency of 75GHz to 110GHz. And absorb microwave radiation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116171303B_ABST
    Figure CN116171303B_ABST
Patent Text Reader

Abstract

Disclosed is a composite comprising: about 50% to about 97% by weight of a thermoplastic resin, wherein the thermoplastic resin comprises a polyester; and about 3% to about 15% by weight of a carbon-based filler, wherein the carbon-based filler has a carbon content of about 500 to about 1000 m 2 / g of main surface area, wherein the composite exhibits a dielectric constant ε' between 5 and 30 and a dissipation loss ε" between 0.5 and 45 when measured at a frequency between about 10 and about 120 GHz. When observed at a frequency of about 75 GHz to 110 GHz according to a free space method, a molded sample of the composite exhibits a reflected power percentage of at least 15% when measured in transmission mode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to materials that exhibit microwave absorbing properties, and in particular to materials that exhibit microwave absorbing properties for automotive radar sensor applications. Background Art

[0002] The automotive industry is increasingly adopting electronic radar sensors to provide driver assistance with features such as adaptive cruise control, parking / lane change assistance, back-up warning, blind spot detection, collision avoidance, etc. To ensure the proper operation of these sensors, these devices must be protected from potential spurious sources of electromagnetic radiation. Microwave radiation from about 1 gigahertz (GHz) (300 millimeters (mm) wavelength) to 300 GHz frequencies (1 mm wavelength) is the most common source of electromagnetic energy used in the operation of radar sensors for automotive applications. Metals (aluminum, stainless steel, etc.), polymer composites containing metal fillers (e.g., aluminum sheets, stainless steel fibers, and silver-coated polyamide fibers), metallized coatings, inherently conductive polymers (polyacetylene, polypyrrole, polythiophene, polyaniline, etc.), silicon carbide, ferrites (iron (III) oxide and nickel Fe 2 O 3 +Ni / Zinc Zn / Cadmium Cd / Cobalt Co oxide) and Iron Carbide are some of the materials used to shield automotive radar sensors from destructive microwave electromagnetic radiation.

[0003] Metals are the most common materials used for microwave (MW) shielding, but they are heavy and expensive. Metals also require complex processing to be shaped into the final component. Polymers or carbon composites are generally preferred due to their lower density, lower cost, ease of shaping, and ease of manufacturing into large volume molded parts. Further, carbon fillers can be used in the composite to capture microwave radiation in the enclosure wall, thereby protecting the electronic sensors in the cavity. For materials used in microwave shielding, moderate electrical conductivity and large dielectric and magnetic losses are generally required. Aspects of the present disclosure address these and other needs. Summary of the invention

[0004] Aspects of the present disclosure are directed to a composite comprising: about 50 wt % to about 97 wt % of a thermoplastic resin, wherein the thermoplastic resin comprises a polyester; and about 3 wt % to about 15 wt % of a carbon-based filler, wherein the carbon-based filler has a carbon content of about 500 to about 1000 m2 / g (m 2 / g) of the primary surface area, wherein the combined weight percentage values ​​of all components do not exceed 100 weight percent, and all weight percentage values ​​are based on the total weight of the composite. When measured at a frequency between about 10 and about 120 GHz, the composite exhibits a dielectric constant ε' between 5 and 30 and a dissipation loss ε" between 0.5 and 45. When observed at a frequency of about 75 GHz to 110 GHz according to the Free Space method, a molded sample of the composite exhibits a reflected power percentage of at least 15% when measured in transmission mode. BRIEF DESCRIPTION OF THE DRAWINGS

[0005] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate several aspects and, together with the description, serve to explain the principles of the disclosure.

[0006] Figure 1 Table 1 is presented, including the formulations of CE-1, CE-2, and EX-1 to EX-3.

[0007] Figure 2 Table 2 including the properties of the carbon black additives is presented.

[0008] Figure 3A Table 3A is presented, including the mechanical, impact, thermal, physical, and electrical properties of EX-1 to EX-3; Figure 3B Table 3B is presented, including the mechanical, impact, thermal, physical, and electrical properties of CE-1 and CE-2; Figure 3C Table 3B for CE-1 and CE-2 is presented.

[0009] Figure 4 Table 4 is presented, including the surface resistivity and volume resistivity of CE-1, CE-2, EX-2, and EX-3.

[0010] Figure 5 Schematic diagrams of the transmission mode and metal-backed reflection mode of the free-space method for determining the dielectric constant ε' and dissipation losses ε" are presented, respectively.

[0011] Figure 6 Table 5 is presented, including the values ​​of the imaginary part ε" and the real part ε' of each of CE-1, CE-2, EX-2 and EX-3, and the dissipation factor tan δ (ε" / ε').

[0012] Figure 7 Table 6 is presented, including reflection loss values ​​(in decibels, dB) at example frequencies 75 GHz, 92.5 GHz, and 110 GHz.

[0013] Fig. 8A A graph showing the real ε' and imaginary ε" parts of the complex dielectric constant of comparative sample CE-1 at frequencies from 18 GHz to 26.5 GHz (K-band) is shown. Figure 8B A graph showing the attenuation constant values ​​(in decibels per centimeter dB / cm) of comparative sample CE-1 at frequencies from 18 GHz to 26.5 GHz (K-band) is shown. Figure 8C A graphical representation of the shielding effectiveness (in dB) of comparative sample CE-1 at frequencies from 18 GHz to 26.5 GHz (K-band) is shown. Fig.8D A graph showing the return loss (in dB) of comparative sample CE-1 in metal-backed reflection mode at frequencies from 18 GHz to 26.5 GHz (K-band) is shown.

[0014] Fig. 9A A graph showing the real ε' and imaginary ε" parts of the complex dielectric constant of comparative sample CE-2 at frequencies from 18 GHz to 26.5 GHz (K-band) is shown. Fig. 9B A graph showing the attenuation constant values ​​(in dB / cm) of comparative sample CE-2 at frequencies (K-band) from 18 GHz to 26.5 GHz. Fig. 9C A graphical representation of the shielding effectiveness (in dB) of comparative sample CE-2 at frequencies from 18 GHz to 26.5 GHz (K-band) is shown. Fig.9D A graph showing the return loss (in dB) of comparative sample CE-2 in metal back reflection mode at frequencies from 18 GHz to 26.5 GHz (K-band) is shown.

[0015] Fig. 10A A graph showing the real ε' and imaginary ε" parts of the complex dielectric constant of the sample EX-2a of the present invention at frequencies from 18 GHz to 26.5 GHz (K-band) is shown. Fig. 10B A graphical representation of the attenuation constant values ​​(in dB / cm) of the inventive sample EX-2a at frequencies from 18 GHz to 26.5 GHz (K-band) is shown. Fig. 10C A graphical representation of the shielding effectiveness (in dB) of sample EX-2a of the present invention at frequencies from 18 GHz to 26.5 GHz (K-band) is shown. Fig. 10D A graph showing the return loss (in dB) of sample EX-2a of the present invention in the metal back reflection mode at frequencies between 18 GHz and 26.5 GHz (K-band) is shown.

[0016] Fig.11AA graph showing the real ε' and imaginary ε" parts of the complex dielectric constant of the sample EX-2b of the present invention at frequencies from 18 GHz to 26.5 GHz (K-band) is shown. Fig. 11B A graphical representation of the attenuation constant values ​​(in dB / cm) of the sample EX-2b of the present invention at frequencies from 18 GHz to 26.5 GHz (K-band) is shown. Fig. 11C A graphical representation of the shielding effectiveness (in dB) of sample EX-2b of the present invention at frequencies from 18 GHz to 26.5 GHz (K-band) is shown. Fig.11D A graph showing the return loss (in dB) of sample EX-2b of the present invention in the metal back reflection mode at frequencies between 18 GHz and 26.5 GHz (K-band) is shown.

[0017] Fig. 12A A graph showing the real ε' and imaginary ε" parts of the complex dielectric constant of the sample EX-3a of the present invention at frequencies from 18 GHz to 26.5 GHz (K-band) is shown. Fig. 12B A graph showing the attenuation constant values ​​(in dB / cm) of the inventive sample EX-3a at frequencies from 18 GHz to 26.5 GHz (K-band) is shown. Fig. 12C A graphical representation of the shielding effectiveness (in dB) of sample EX-3a of the present invention at frequencies from 18 GHz to 26.5 GHz (K-band) is shown. Fig.12D A graph showing the return loss (in dB) of sample EX-3a of the present invention in the metal back reflection mode at frequencies from 18 GHz to 26.5 GHz (K-band) is shown.

[0018] Fig.13A A graph showing the real ε' and imaginary ε" parts of the complex dielectric constant of the sample EX-3b of the present invention at frequencies from 18 GHz to 26.5 GHz (K-band) is shown. Fig. 13B A graphical representation of the attenuation constant values ​​(in dB / cm) of the sample EX-3b of the present invention at frequencies from 18 GHz to 26.5 GHz (K-band) is shown. Fig. 13C A graphical representation of the shielding effectiveness (in dB) of sample EX-3b of the present invention at frequencies from 18 GHz to 26.5 GHz (K-band) is shown. Fig.13D A graph showing the return loss (in dB) of sample EX-3b of the present invention in the metal back reflection mode at frequencies between 18 GHz and 26.5 GHz (K-band) is shown.

[0019] Fig.14 Table 7 is presented, including the formulations of samples EX-4, EX-5, EX-6, EX-7, CE3, and EX-2.

[0020] Fig.15Table 8 is presented, including the values ​​of the real ε' and imaginary ε" parts of the complex dielectric constant, attenuation constant, total shielding effectiveness, measured reflection loss (metal back reflection mode), calculated reflection loss (metal back reflection mode), absorbed power percentage (metal back reflection mode), reflected power percentage (transmission mode), absorbed power percentage (transmission mode), and transmitted power percentage (transmission mode) of samples EX-4, EX-5, EX-6, EX-7, CE3, and EX-2 observed at 77 GHz.

[0021] Fig.16A Presented is a graph of the dissipation factor tan δ (ε" / ε') observed at 77 GHz for samples EX-4, EX-5, EX-6, EX-7, CE3, and EX-2. Fig. 16B Presented are graphs of the real and imaginary parts of the dielectric constants observed at 77 GHz for samples EX-4, EX-5, EX-6, EX-7, CE3, and EX-2.

[0022] Fig.17 A graph showing the attenuation constant values ​​observed at 77 GHz for samples EX-4, EX-5, EX-6, EX-7, CE3, and EX-2.

[0023] Fig.18 Shown is a graphical representation of the total shielding effectiveness (SE) values ​​observed at 77 GHz for samples EX-4, EX-5, EX-6, EX-7, CE3, and EX-2.

[0024] Fig.19 A graph showing the percentage of reflected power (transmission mode), the percentage of absorbed power (transmission mode), and the percentage of transmitted power (transmission mode) observed at 77 GHz for EX-4, EX-5, EX-6, EX-7, CE3, and EX-2.

[0025] Fig. 20 A graph showing the percent absorbed power (metal back reflection mode) and percent absorbed power (transmission mode) observed at 77 GHz for samples EX-4, EX-5, EX-6, EX-7, CE3, and EX-2.

[0026] Fig.21 Table 9 is presented, including values ​​of volume resistivity and surface resistivity for samples EX-4, EX-5, EX-6, EX-7, CE-3, and EX-2.

[0027] Fig.22A is a graphical representation of the volume resistivity of samples EX-4, EX-5, EX-6, EX-7, CE-3, and EX-2 as a function of carbon loading; Fig. 22BPlot of surface resistivity as a function of carbon loading for samples EX-4, EX-5, EX-6, EX-7, CE-3, and EX-2.

[0028] Fig.23A is a graphical representation of the real part of the dielectric constant of samples EX-4, EX-5, EX-6, EX-7, and CE-3 observed in the K band; Fig. 23B Graph of the real part of the dielectric constant observed in the W band for samples EX-4, EX-5, EX-6, EX-7, and CE-3.

[0029] Fig.24A is a graphical representation of the imaginary part of the dielectric constant of samples EX-4, EX-5, EX-6, EX-7, and CE-3 observed in the K band; Fig. 24B Graph of the imaginary part of the dielectric constant observed in the W band for samples EX-4, EX-5, EX-6, EX-7, and CE-3.

[0030] Fig.25A is a graphical representation of the reflection losses observed in the K band for samples EX-4, EX-5, EX-6, EX-7, and CE-3 measured in the metal back reflection mode; Fig.25B Graph of the reflection losses observed in the W band for samples EX-4, EX-5, EX-6, EX-7, and CE-3 measured in metal back reflection mode.

[0031] Fig.26A is a graphical representation of the decay constant values ​​of samples EX-4, EX-5, EX-6, EX-7, and CE-3 observed in the K band; Fig.26B Graph showing the decay constant values ​​observed in the W band for samples EX-4, EX-5, EX-6, EX-7, and CE-3.

[0032] Fig.27A is a graphical representation of the total shielding effectiveness of samples EX-4, EX-5, EX-6, EX-7, and CE-3 observed in the K band; Fig.27B Graph of the total shielding effectiveness observed in the W band for samples EX-4, EX-5, EX-6, EX-7, and CE-3.

[0033] Fig.28A is a graphical representation of the percentage of absorbed power in transmission mode observed in the K band for samples EX-4, EX-5, EX-6, EX-7, and CE-3; Fig.28B Plot of the percentage of absorbed power observed in the W band for samples EX-4, EX-5, EX-6, EX-7, and CE-3 in transmission mode.

[0034] Fig.29Ais a graphical representation of the percentage of absorbed power observed in the K band for samples EX-4, EX-5, EX-6, EX-7, and CE-3 in the metal back reflection mode; Fig.29B Graph of the percentage of absorbed power observed in the W band for samples EX-4, EX-5, EX-6, EX-7, and CE-3 in the metal back reflection mode.

[0035] Fig.30 A graph showing the percent power of sample CE-3 measured in transmission mode at frequencies from 75 GHz to 110 GHz is shown.

[0036] Fig.31 A graph showing the percent power measured in transmission mode at frequencies from 75 GHz to 110 GHz for sample EX-4 is shown.

[0037] Fig.32 A graph showing the percent power of sample EX-5 measured in transmission mode at frequencies from 75 GHz to 110 GHz.

[0038] Fig.33 A graph showing the percent power measured in transmission mode at frequencies from 75 GHz to 110 GHz for sample EX-6 is shown.

[0039] Fig.34 A graph showing the percent power measured in transmission mode at frequencies from 75 GHz to 110 GHz for sample EX-7 is shown.

[0040] Fig.35 A graph showing the percent power measured in transmission mode at frequencies from 75 GHz to 110 GHz for sample EX-2 is shown.

[0041] Fig.36 A schematic diagram of a two-shot injection molding process is shown.

[0042] Fig.37 Schematic diagram showing the two injection units of a two-shot injection molding process.

[0043] Fig.38 Formulations CE-4, EX-8, EX-9 of Table 10 are shown.

[0044] Fig.39 Tables 11, 12 and 13 are presented showing the steady state shear viscosities of the formulations.

[0045] Fig.40 Tables 14 and 15 are presented showing the mechanical properties and volume and surface resistivities of CE-4, EX-8, and EX-9.

[0046] Fig.41A Table 16 is presented, showing the formulations of comparative samples CE-5 and CE-6. Fig.41B Tables 17 and 18 are presented, showing the respective properties of CE-5 and CE-6.

[0047] Fig.42 Tables 19, 20 and 21 are presented showing the physical and resistivity properties of the samples.

[0048] Fig.43A and 43B The dielectric constant and loss tangent of CE-5 are presented (respectively). Fig.44A and 44B The S-parameter magnitude (dB) and insertion loss (dB) of CE-5 are presented. Fig.45A and 45B The return loss (dB) and attenuation constant (dB / cm) of CE-5 are presented. Fig.46A and 46B The shielding effectiveness (dB) and metal back reflection loss (dB) of CE-5 are presented. Fig.47A and 47B The percentage power in CE-5 transmission mode and the percentage power in metal back reflection mode are presented (respectively).

[0049] Fig.48A and Fig.48B The dielectric constant and loss tangent of EX-8 are presented (respectively). Fig.49A and Fig.49B The S-parameter magnitude (dB) and insertion loss (dB) of the EX-8 are presented. Fig.50A and Fig.50B The return loss (dB) and attenuation constant (dB / cm) of the EX-8 are presented. Fig.51A and Fig.51B The shielding effectiveness (dB) and metal back reflection loss (dB) of EX-8 are presented. Fig.52A and Fig.52B The percentage power in EX-8 transmission mode and the percentage power in metal back reflection mode are presented (respectively).

[0050] Fig.53A and Fig.53B The dielectric constant and loss tangent of EX-9 are presented (respectively). Fig.54A and Fig.54B The S-parameter magnitude (dB) and insertion loss (dB) of the EX-9 are presented. Fig.55A and Fig.55B The return loss (dB) and attenuation constant (dB / cm) of the EX-9 are presented. Fig.56Aand Fig.56B The shielding effectiveness (dB) and metal back reflection loss (dB) of EX-9 are presented. Fig.57A and Fig.57B The percentage power in EX-9 transmission mode and the percentage power in metal back reflection mode are presented (respectively). DETAILED DESCRIPTION

[0051] The present disclosure relates to microwave shielding and absorbing composite materials. Electronic radar sensors are used in the automotive industry to assist drivers in various operations, including cruise control, lane change assistance, automatic parking, and blind spot detection. These sensors must be protected from electromagnetic interference that may impair their normal operation. Metals such as aluminum and stainless steel are commonly used as microwave shielding materials, but they are heavy, expensive, and require complex processing to be shaped into final components. Polymer / carbon composites may be more ideal as lower density, lower cost alternatives. Polymer / carbon composites are also easier to mold and manufacture into large volume molded parts. The carbon filler of the composite can isolate microwave radiation in the enclosure wall to protect the electronic sensors in the cavity.

[0052] Therefore, moderate conductivity and large dielectric and magnetic losses are some of the characteristics required of materials used in microwave shielding. The present disclosure provides a series of polymer-based materials that include carbon as a microwave absorbing filler and have a polymer / filler ratio that provides a suitable balance between conductivity and microwave absorption efficiency.

[0053] As demonstrated herein, composites with relatively high electrical conductivity (corresponding to a volume resistivity of less than about 100 ohm-cm) behave more like metals dielectrically than plastics, and therefore exhibit microwave reflective properties similar to metals. Radar absorbing materials are currently sold commercially primarily in the form of elastomer-based flexible sheets or blankets, liquid coatings, and closed-cell polymer foams. The present disclosure provides thermoplastic-based carbon-filled materials that are rigid and have high modulus, retain a certain shape when molded, and are suitable as interior or exterior components to capture or isolate electromagnetic radiation in automotive sensor applications.

[0054] Carbon fillers (including but not limited to powders, flakes, fibers, nanotubes) are currently used to impart electromagnetic interference properties to polymers that, when unfilled, are largely transparent (non-absorbing, non-reflective) to microwave radiation. For example, when used in an under-the-hood automotive housing, a polymer-carbon composite can protect a radar sensor located inside the housing, thereby preventing electromagnetic radiation from external or even internal sources from degrading the electronic performance of the sensor. In addition, carbon-containing elastomers (such as silicones, polyurethanes, and nitrile rubbers, etc.) can be used as high-loss protective blankets to attenuate resonant frequencies generated by normal operation of the sensor within the cavity. The present disclosure describes thermoplastic-based carbon-filled materials that are rigid and have high modulus, retain a certain shape when molded, and they can be used as internal or external components to capture electromagnetic radiation in automotive sensor applications.

[0055] Before disclosing and describing the compounds, compositions, articles, systems, devices and / or methods of the present invention, it should be understood that they are not limited to specific synthetic methods unless otherwise specified, or to specific reagents unless otherwise specified, as this can of course vary. It should also be understood that the terms used herein are used only for the purpose of describing specific aspects and are not intended to be limiting. The present disclosure encompasses various combinations of elements of the present disclosure, for example, combinations of elements from dependent claims that are dependent on the same independent claim.

[0056] Furthermore, it should be understood that, unless otherwise expressly stated, it is not intended that any method described herein be interpreted as requiring that its steps be performed in a particular order. Therefore, in the event that a method claim does not actually recite the order in which its steps are to be followed or that the steps are not otherwise specifically stated in the claim or specification to be limited to a particular order, no order is intended to be inferred in any respect. This applies to any possible non-express basis for interpretation, including: logical issues regarding the arrangement of steps or operational flows; ordinary meaning derived from grammatical organization or punctuation; and the number or type of embodiments described in the specification.

[0057] Compound

[0058] Aspects of the present disclosure relate to composites comprising a thermoplastic polymer component (including polyester) and a carbon filler. The thermoplastic polymer component may include any suitable thermoplastic polymer. Examples include, but are not limited to, polycarbonates, polyetherimides, liquid crystal polymers, polyamides, polyimides, polyesters, copolymers thereof, blends thereof, or combinations thereof.

[0059] In certain aspects, the composite has a surface resistivity of at least 30 ohms / square (Ω / sq) and a volume resistivity of at least 10 ohms-centimeter (Ω·cm) when measured according to ASTM D257 and using a specimen having a thickness of 0.125 inches (3.175 mm). Further, the composite may exhibit a dielectric constant Dk (real part ε' of the complex dielectric constant) of about 5 to about 30, and may exhibit a dissipation loss (imaginary part ε" of the complex dielectric constant) of about 0.5 to 45. The ratio of dissipation loss to dielectric constant ε" / ε' of the composite (referred to as dissipation factor Df or tan δ) may be from about 0.01 to about 2.

[0060] The molded panels formed from the disclosed composites may be suitable as exterior or interior components of electrical devices used in microwave absorption or shielding applications. Experiments have shown that panels molded from the materials of the present invention are capable of reflecting at least 14% of incident microwave radiation having a frequency of about 75 GHz to about 110 GHz. The molded panels may have a thickness of 1 millimeter (mm) to about 5 mm. In various examples, the molded panels may have a thickness of 0.125 inches (3.175 mm).

[0061] In various aspects, the present disclosure provides composites that can be used to make housings that can isolate electronic sensors from damaging microwave electromagnetic energy. Dielectric properties of these materials have been evaluated at frequencies of about 10 GHz to 120 GHz, such as complex permittivity, reflection and insertion losses, attenuation and shielding effectiveness, etc. Further disclosed herein are radar sensor components (boards, housings, covers, etc.) made from these materials, as well as articles (sensors, cameras, electronic control units (ECUs)) made from these components.

[0062] In yet further aspects, the composite may include a thermoplastic polymer component (including polyester), a carbon filler, and a glass fiber filler. The composite may include about 50% to about 97% by weight of a thermoplastic resin, about 5% to about 15% by weight of a carbon-based filler, and about 0.01% to about 25% by weight of a glass fiber filler. When tested according to ASTM D638, such a glass fiber-filled composite may exhibit a tensile modulus of less than 9,000 MPa, a tensile modulus of less than 1.0×10 11 A volume resistivity of ohm-cm, a dielectric constant ε' between 5 and 30 and a dissipation loss ε" between 0.5 and 45 measured at a frequency between about 10 and about 120 GHz, and a molded sample of the composite can exhibit an absorbed power percentage of at least 55% when measured in transmission mode when observed according to a free space method at a frequency of about 10 GHz to 120 GHz.

[0063] In some aspects, a composite comprising: about 50 wt % to about 97 wt % of a thermoplastic resin, wherein the thermoplastic resin comprises a polyester; and about 3 wt % to about 15 wt % of a carbon black filler, wherein the carbon black filler has a carbon black content of about 500 to about 1000 m 2 / g of main surface area, wherein the composite exhibits a dielectric constant ε' between 5 and 30 and a dissipation loss ε" between 0.5 and 45 when measured at a frequency between about 10 and about 120 GHz, wherein a molded sample of the composite exhibits a reflected power percentage of at least 15% when measured in transmission mode when observed at a frequency of about 75 GHz to 110 GHz according to a free space method, and wherein the combined weight percentage values ​​of all components do not exceed 100 weight percent, and all weight percentage values ​​are based on the total weight of the composite.

[0064] Further disclosed is a component of an automotive radar sensor, such as a plate, housing or cover, which is molded from a material comprising a polymer and a carbon filler, wherein the molded component has a certain design, average thickness, microwave absorption efficiency, absorption bandwidth, and certain surface and volume resistivity. Another aspect of the present disclosure is an article, such as a radar sensor, a camera, an ECU, which includes a molded component made of a radar absorbing material, wherein such a molded component has at least two openings to allow microwave radiation to be transmitted between a transmitting antenna and a receiving antenna located in a printed circuit board of the sensor. Automotive radar sensors used for lane change assistance, automatic parking, blind spot detection and collision avoidance typically operate at a frequency of 24 GHz, and those automotive radar sensors used for adaptive cruise control operate at a frequency of 77 GHz. Therefore, the composites of the present disclosure have been observed in the K band including the 24 GHz frequency and the W band including the 77 GHz frequency.

[0065] Thermoplastic resin

[0066] On the one hand, polymer composition can include polymer base resin.In various fields, described polymer base resin can include thermoplastic resin or thermosetting resin.Described thermoplastic resin can include: polypropylene, polyethylene, copolymer based on ethylene, polyamide, polycarbonate, polyester, polyoxymethylene (POM), polybutylene terephthalate (PBT), polybutylene terephthalate (PET), polycyclohexylene terephthalate (PCT), liquid crystal polymer (LCP), polyphenylene sulfide (PPS), polyphenylene oxide (PPE), polyphenylene oxide-polystyrene blend, polystyrene, high impact modified polystyrene, acrylonitrile-butadiene-styrene (ABS) terpolymer, acrylic polymer, polyetherimide (PEI), polyurethane, polyetheretherketone (PEEK), polymer based on polylactic acid (PLA), polyethersulfone (PES), and combination thereof.Described thermoplastic resin can also include thermoplastic elastomer, for example, elastomer based on polyamide and polyester. The base substrate may also include blends and / or other types of combinations of the above resins. In various aspects, the polymer base resin may also include a thermosetting polymer. Suitable thermosetting resins may include: phenolic resins, urea resins, melamine-formaldehyde resins, urea-formaldehyde latex, xylene resins, diallyl phthalate resins, epoxy resins, aniline resins, furan resins, polyurethanes, or combinations thereof.

[0067] In various aspects of the present disclosure, the thermoplastic resin may include a polyester. For example, the thermoplastic resin may include a polyalkylene ester (polyester), such as a polyalkylene terephthalate polymer.

[0068] Polyesters have repeating units of the following formula (A):

[0069]

[0070] Wherein T is a residue derived from terephthalic acid or its chemical equivalent (equivalent), and D is a residue derived from the polymerization of ethylene glycol, butanediol, especially 1,4-butanediol or its chemical equivalent. The chemical equivalents of diacids include dialkyl esters, such as dimethyl esters, diaryl esters, anhydrides, salts, acid chlorides, acid bromides, etc. The chemical equivalents of ethylene glycol and butanediol include esters, such as dialkyl esters, diaryl esters, etc. In addition to units derived from terephthalic acid or its chemical equivalents and ethylene glycol or butanediol, especially 1,4-butanediol or its chemical equivalents, other T and / or D units may also be present in the polyester, provided that the type or amount of such units does not significantly adversely affect the desired properties of the thermoplastic composition. The poly(alkylene arylate) may have a polyester structure according to formula (A), wherein T comprises a group derived from an aromatic dicarboxylic acid ester, an alicyclic dicarboxylic acid or a derivative thereof.

[0071] Examples of particularly useful T groups include, but are not limited to, 1,2-, 1,3-, and 1,4-phenylene; 1,4- and 1,5-naphthylene; cis- or trans-1,4-cyclohexylene, etc. Specifically, when T is 1,4-phenylene, the poly(alkylene arylate) is a poly(alkylene terephthalate). In addition, for poly(alkylene arylate), particularly useful alkylene groups D include, for example, ethylene, 1,4-butylene, and bis-(alkylene-disubstituted cyclohexanes), including cis- and / or trans-1,4-(cyclohexylene) dimethylene.

[0072] Examples of polyalkylene terephthalates include polybutylene terephthalate (PET), poly(1,4-butylene terephthalate) (PBT), and poly(propylene terephthalate) (PPT). Also useful are poly(alkylene naphthoates), such as poly(ethylene naphthalate) (PEN) and poly(butylene naphthalate) (PBN). A useful poly(cycloalkylene diester) is poly(cyclohexanedimethylene terephthalate) (PCT). Combinations comprising at least one of the foregoing polyesters may also be used.

[0073] Copolymers comprising repeating ester units of alkylene terephthalates with other ester groups may also be useful. Useful ester units may include different alkylene terephthalate units, which may be present in the polymer chain as individual units or as blocks of poly(alkylene terephthalates). Specific examples of such copolymers include poly(cyclohexanedimethylene terephthalate)-co-poly(ethylene terephthalate), abbreviated as PETG (wherein the polymer includes greater than or equal to 50 mol % of poly(ethylene terephthalate)), and abbreviated as PCTG (wherein the polymer contains greater than 50 mol % of poly(1,4-cyclohexanedimethylene terephthalate)). Poly(cycloalkylene diesters) may also include poly(alkylene cyclohexane dicarboxylates). Among them, a specific example is poly(1,4-cyclohexanedimethanol ester of 1,4-cyclohexane dicarboxylate) (PCCD) having repeating units of formula (B):

[0074]

[0075] Wherein, as described using formula (A), R 2 is a 1,4-cyclohexanedimethylene group derived from 1,4-cyclohexanedimethanol, and T is a cyclohexane ring derived from a cyclohexanedicarboxylate or a chemical equivalent thereof, and may comprise a cis isomer, a trans isomer, or a combination comprising at least one of the foregoing isomers.

[0076] In another aspect, the composition may further comprise poly(1,4-butylene terephthalate) or "PBT" resin. PBT may be obtained by polymerizing a glycol component (at least 70 mol %, preferably at least 80 mol % of which consists of tetramethylene glycol) and an acid or ester component (at least 70 mol %, preferably at least 80 mol % of which consists of terephthalic acid and / or a polyester-forming derivative of terephthalic acid). Commercial examples of PBT include poly(1,4-butylene terephthalate) available under the trade name VALOX TM 315. VALOX TM 195 and VALOX TM 176 of those obtained by SABIC TM The PBT resin is manufactured to have an intrinsic viscosity of 0.1 deciliter / gram (dl / g) to about 2.0 dl / g (or 0.1 dl / g to 2 dl / g) when measured in a 60:40 phenol / tetrachloroethane mixture or similar solvent at 23 degrees Celsius (° C.) to 30° C. In one aspect, the PBT resin has an intrinsic viscosity of 0.1 dl / g to 1.4 dl / g (or about 0.1 dl / g to about 1.4 dl / g), specifically 0.4 dl / g to about 1.4 dl / g (or about 0.4 dl / g to about 1.4 dl / g).

[0077] As described herein, the composition may include about 40% to about 97% by weight of a polyalkylene polymer. In further embodiments, the composition may include about 50% to about 97% by weight of a polyalkylene polymer, or about 40% to about 97% by weight of a polyalkylene polymer, or about 55% to about 97% by weight of a polyalkylene polymer, or about 60% to about 97% by weight of a polyalkylene polymer, or about 70% to about 97% by weight of a polyalkylene polymer, or about 40% to about 95% by weight of a polyalkylene polymer, or about 55% to about 95% by weight of a polyalkylene polymer, or about 60% to about 95% by weight of a polyalkylene polymer, or about 75% to about 97% by weight of a polyalkylene polymer.

[0078] In a further aspect, the thermoplastic resin may comprise a polycarbonate copolymer. The polycarbonate may comprise any polycarbonate material or mixture of materials, for example, as described in U.S. Pat. No. 7,786,246 (which is incorporated herein in its entirety for the specific purpose of disclosing various polycarbonate compositions and methods). The term polycarbonate may be further defined as a composition having repeating structural units of formula (1):

[0079]

[0080] Where R 1 At least 60% of the total number of radicals are aromatic organic radicals and the remainder are aliphatic, alicyclic or aromatic radicals. In a further aspect, each R1 is an aromatic organic group, and more preferably a group of formula (2):

[0081] ─A 1 ─Y 1 ─A 2 (2)

[0082] Among them A 1 and A 2 Each of is a monocyclic divalent aromatic group, and Y 1 A 1 With A 2 A bridging radical having one or two atoms is separated. In various aspects, an atom separates A 1 With A 2 For example, this type of group includes, but is not limited to, groups such as ─O─, ─S─, ─S(O)─, ─S(O 2 )─, ─C(O)─, methylene, cyclohexyl-methylene, 2-[2.2.1]-bicycloheptylene, ethylene, isopropylene, neopentylene, cyclohexylene, cyclopentadecylene, cyclododecylene and adamantylene. Bridging group Y 1 Preferred is a hydrocarbon group or a saturated hydrocarbon group, such as a methylene group, a cyclohexylene group or an isopropylene group.

[0083] In various further aspects, "polycarbonate" and "polycarbonate resin" as used herein further include homopolycarbonates, polycarbonates including different R 1 The invention also includes copolymers of carbonate units and other types of polymer units (e.g., ester units, polysiloxane units), and combinations comprising at least one of homopolycarbonate and copolycarbonate. As used herein, "combination" includes blends, mixtures, alloys, reaction products, etc.

[0084] Non-limiting examples of polysiloxane-polycarbonate copolymers may include various copolymers available from SABIC. In one aspect, the polysiloxane-polycarbonate copolymer may contain 6 wt% polysiloxane content, based on the total weight of the polysiloxane-polycarbonate copolymer. In various aspects, using gel permeation chromatography with bisphenol A polycarbonate absolute molecular weight standards, 6 wt% polysiloxane block copolymers may have a weight average molecular weight (Mw) of about 23,000 to 24,000 Daltons. In certain aspects, 6 wt% siloxane polysiloxane-polycarbonate copolymers may have a molecular weight of about 10 cm at 300°C / 1.2 kg. 3 / 10 minutes melt volume flow rate (MVR) (see C9030T, a copolymer with 6 wt% polysiloxane content available from SABIC Innovative Plastics as "transparent" EXL C9030T resin polymer). In another example, the polysiloxane-polycarbonate block may contain 20 wt% polysiloxane, based on the total weight of the polysiloxane-polycarbonate block copolymer. For example, a suitable polysiloxane-polycarbonate copolymer may be a bisphenol A polysiloxane-polycarbonate copolymer end-capped with p-cumylphenol (PCP) and having a 20% polysiloxane content (see C9030P, commercially available from SABIC as "opaque" EXL C9030P). In various aspects, the 20% polysiloxane block copolymer can have a weight average molecular weight of about 29,900 Daltons to about 31,000 Daltons when tested against polycarbonate standards using gel permeation chromatography (GPC) on a crosslinked styrene-divinylbenzene column and calibrated to a polycarbonate reference using a UV-VIS detector set at 264 nm for a 1 mg / ml sample eluted at a flow rate of about 1.0 ml / minute. In addition, the 20% polysiloxane block copolymer can have a molecular weight of 7 cm at 300°C / 1.2 kg. 3 The siloxane polymer may have a melt volume rate (MVR) of 100 Å / 10 minutes and may exhibit siloxane domains having a size ranging from about 5 micrometers to about 20 micrometers (μm).

[0085] Certain aspects of the composition include from about 50 wt % to about 97 wt % of a thermoplastic resin, or from about 40 wt % to about 97 wt % of a polymer base resin, or from about 55 wt % to about 97 wt % of a polymer base resin, or from about 60 wt % to about 97 wt % of a polymer base resin, or from about 70 wt % to about 97 wt % of a polymer base resin, or from about 40 wt % to about 95 wt % of a polymer base resin, or from about 55 wt % to about 95 wt % of a polymer base resin, or from about 60 wt % to about 95 wt % of a polymer base resin, or from about 75 wt % to about 97 wt % of a polymer base resin.

[0086] Carbon-based fillers

[0087] In various aspects, the composite comprises a carbon-based filler. Generally, the carbon-based filler may include carbon fiber, carbon powder, graphite, graphene, carbon platelet (carbon platelet, carbon platelet) or carbon nanotube. The carbon-based filler may further refer to a granular carbonaceous material (carbonaceous meterial), such as furnace black, thermal black, surface modified carbon black, heat-treated carbon black, activated carbon, graphite, carbon fiber, carbon nanotube, or a combination thereof. According to certain aspects of the present disclosure, the carbon-based filler includes carbon powder. In addition, the carbon-based filler may include carbon powder, and may be free of or substantially free of carbon nanotubes, carbon platelets or carbon fibers.

[0088] In one example, the carbon-based filler is carbon black. Carbon black may refer to an amorphous form of carbon with a high surface area to volume ratio. Further, depending on manufacturing conditions, carbon black may include chemically adsorbed oxygen complexes (e.g., carboxylic acids, quinones, lactones, phenolic groups, etc.) on its surface to varying degrees. Carbon black properties such as particle size, structure, and purity may vary depending on the type of carbon black selected. In one aspect, carbon black can be well dispersed in the polymer phase, maintaining the integrity of its structure or network, and having a consistent particle size.

[0089] The conductivity of the polymer-carbon black composite can be measured using the surface resistivity (SR) of the conductive film. In one aspect, the conductivity can depend on the polymer phase, the type of conductive carbon black, the loading of the conductive carbon black, and the dispersion of the conductive carbon black. The conductive carbon black can be furnace black or acetylene black or additional conductive carbon black. Conductive carbon black such as furnace black or acetylene black has a surface resistivity of 1 to 10. 2 High volume resistivity in the ohm-cm range. This carbon black can exhibit a volume resistivity of about 500 m2 / g (m 2 / g) to about 1000m 2 / g BET (Brunauer, Emmett and Teller) primary surface area, which can be referred to as high structure or high surface area carbon black. For reference, low structure carbon black can have a relatively low surface area, for example, less than 300 m 2 / g, less than 200m 2 / g or less than 150m 2 / g. In another aspect, the carbon black powder exhibits an oil absorption of about at least 100 milliliters (ml) / 100 grams (g). In a specific aspect, the conductive filler includes ENSACO available from Earache Europe or Imerys Graphite & Carbon Switzerland. TM 350g or 360g toner.

[0090] In some aspects, the polymer composition may include a carbon-based filler having at least one dimension of a specific size. The carbon-based filler may include a powder having a specific particle size distribution. For example, the carbon-based filler (e.g., carbon black) may have at least one dimension less than 100nm. In some aspects, the carbon-based filler may have a specific diameter. A polymer composition, wherein the carbon-based filler may include a powder of a certain particle size. For example, the carbon-based filler may have a primary particle size of 10 nanometers (nm) to 50nm. In a further aspect, the carbon-based filler may have a DBP absorption of about 80 milliliters / 100 grams (ml / 100g) to 500ml / 100g.

[0091] In some aspects, the composition may include about 0.01% to about 15% by weight of a carbon-based filler, based on the total weight of the polymer composition. The ratio of thermoplastic resin to carbon filler may be about 32:1 to about 6:1 or about 24:1 to about 6:1. In a further aspect, the composition may include about 4% to about 8% by weight, or about 0.01% to about 3% by weight, or about 0.1% to about 3% by weight, or about 0.01% to about 2.5% by weight, or about 0.5% to about 3% by weight of a carbon-based filler, or about 1% to about 3% by weight of a carbon-based filler, or about 0.5% to about 2.5% by weight of a carbon-based filler.

[0092] additive

[0093] The disclosed thermoplastic composition may include one or more conventional additives for making molded thermoplastic parts, provided that the optional additives do not adversely affect the desired properties of the resulting composition. A mixture of optional additives may also be used. These additives may be mixed at a suitable time during the mixing of the components used to form the composite mixture. Exemplary additives may include ultraviolet agents, ultraviolet stabilizers, heat stabilizers, antistatic agents, antimicrobial agents, anti-drip agents, radiation stabilizers, pigments, dyes, fibers, fillers, plasticizers, fibers, flame retardants, antioxidants, lubricants, wood, glass and metals, and combinations thereof. According to certain aspects, even with a high level of filler (e.g., greater than 30% by weight of filler, based on the gross weight of the polymer composition), the polymer composition may also maintain mechanical properties and dielectric strength. However, it should be noted that the disclosed composition does not require the addition of a permanent antistatic agent to affect certain properties, such as further reducing the surface and volume resistivity of these materials, and achieving their desired dielectric properties. Therefore, the composition may be free of or substantially free of an antistatic agent. The composition of the present disclosure may be characterized by a relatively large surface area (greater than 500 m2 when tested according to the BET method). 2 / g) of a single conductive filler, namely carbon black, to achieve the disclosed properties.

[0094] The composite disclosed herein may include one or more additional fillers. Fillers may be selected to impart additional impact strength and / or provide additional characteristics, which may be based on the final selected characteristics of the polymer composition. In some aspects, fillers may include inorganic materials, which may include clay, titanium oxide, asbestos fiber, silicate and silicon dioxide powder, boron powder, calcium carbonate, talc, kaolin, sulfide, barium compounds, metals and metal oxides, wollastonite, glass balls, glass fibers, flaked fillers, fibrous fillers, natural fillers and reinforcing agents, and reinforcing organic fibrous fillers. In some aspects, the composite may include glass fiber fillers. For example, the composite may include about 0.01% by weight to about 25% by weight, about 10% by weight to about 25% by weight, about 15% by weight to about 25% by weight of glass fiber fillers, based on the total weight of the composite. In a further aspect, the composite may be free of or substantially free of glass fillers.

[0095] Suitable fillers or reinforcing agents may include, for example, mica, clay, feldspar, quartz, quartzite, perlite, tripoli, diatomaceous earth, aluminum silicate (mullite), synthetic calcium silicate, fused silica, fumed silica, sand, boron nitride powder, borosilicate powder, calcium sulfate, calcium carbonate (such as chalk, limestone, marble and synthetic precipitated calcium carbonate), talc (including fibrous, modular, needle-shaped, and lamellar talc), wollastonite, hollow or solid glass spheres, silicate spheres, hollow microspheres, aluminosilicates or (armospheres), kaolin, whiskers of silicon carbide, aluminum oxide, boron carbide, iron, nickel or copper , continuous and chopped carbon fibers or glass fibers, molybdenum sulfide, zinc sulfide, barium titanate, barium ferrite, barium sulfate, barite, titanium dioxide, aluminum oxide, magnesium oxide, granular or fibrous aluminum, bronze, zinc, copper or nickel, glass flakes, flake silicon carbide, flake aluminum diboride, flake aluminum, steel flakes, natural fillers such as wood flour, fibrous cellulose, cotton, sisal, jute, starch, lignin, ground nut shells or rice husks, reinforcing organic fibrous fillers such as poly (ether ketone), polyimide, polybenzoxazole, poly (phenylene sulfide), polyester, polyethylene, aramid, aromatic polyimide, polyetherimide, polytetrafluoroethylene and poly (vinyl alcohol), and combinations comprising at least one of the foregoing fillers or reinforcing agents. Fillers and reinforcing agents can be coated or surface treated with, for example, silanes to improve adhesion and dispersibility to the polymer matrix. Fillers can generally be used in an amount of 1 to 200 parts by weight, based on 100 parts by weight of the total composition.

[0096] In some aspects, the thermoplastic composition may include a synergist. In various examples, fillers may be used as flame retardant synergists. When added to a flame retardant composition, compared with a comparative composition containing the same amount of all the same ingredients except the synergist, the synergist promotes the improvement of flame retardant properties. Examples of mineral fillers that may be used as synergists are mica, talc, calcium carbonate, dolomite, wollastonite, barium sulfate, silicon dioxide, kaolin, feldspar, barite, etc. or a combination comprising at least one of the aforementioned mineral fillers. Metal synergists, such as antimony oxide, may also be used together with flame retardants. In one example, the synergist may include magnesium hydroxide and phosphoric acid. The mineral filler may have an average particle size of about 0.1 to about 20 microns, particularly about 0.5 to about 10 microns and more particularly about 1 to about 3 microns.

[0097] The thermoplastic composition may include an antioxidant. The antioxidant may include a primary antioxidant or a secondary antioxidant. For example, the antioxidant may include an organic phosphite (salt), such as tris (nonylphenyl) phosphite (salt), tris (2,4-di-tert-butylphenyl) phosphite (salt), bis (2,4-di-tert-butylphenyl) pentaerythritol diphosphite (salt), distearyl pentaerythritol diphosphite (salt), etc.; alkylated monophenol or polyphenol; alkylation reaction products of polyphenols and dienes, such as tetrakis [methylene (3,5-di-tert-butyl-4-hydroxyhydrocinnamate)] methane, etc.; butylation reaction products of p-cresol or dicyclopentadiene; alkylated hydroquinones (class); hydroxylated thiodiphenyl ethers (class); alkylene bisphenols (class); benzyl compounds; β-(3,5- Esters of di-tert-butyl-4-hydroxyphenyl)-propionic acid and monohydric or polyhydric alcohols; esters of β-(5-tert-butyl-4-hydroxy-3-methylphenyl)-propionic acid and monohydric or polyhydric alcohols; esters of thioalkyl or thioaryl compounds, such as distearyl thiopropionate, dilauryl thiopropionate, ditridecyl thiodipropionate, octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, pentaerythritol-tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, etc.; amides of β-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid, etc.; or a combination comprising at least one of the foregoing antioxidants. Antioxidants can generally be used in an amount of 0.01 to 0.5 parts by weight, based on 100 parts by weight of the total composition, excluding any filler.

[0098] In various aspects, the thermoplastic composition may include a release agent. Exemplary release agents may include, for example, metal stearates, stearyl stearate, pentaerythritol tetrastearate, beeswax, montan wax, paraffin wax, etc., or a combination including at least one of the foregoing release agents. The release agent is generally used in an amount of about 0.1 to about 1.0 parts by weight, based on 100 parts by weight of the total composition, excluding any filler.

[0099] In one aspect, the thermoplastic composition may include a heat stabilizer. As an example, the heat stabilizer may include, for example, an organic phosphite such as triphenylphosphite, tris-(2,6-dimethylphenyl)phosphite, tris-(mixed mono- and di-nonylphenyl)phosphite, etc.; a phosphonate such as dimethylphenylphosphonate, etc.; a phosphate such as trimethylphosphonate, etc., or a combination including at least one of the foregoing heat stabilizers. The heat stabilizer may generally be used in an amount of 0.01 to 0.5 parts by weight, based on 100 parts by weight of the total composition, excluding any filler.

[0100] In a further aspect, a light stabilizer may be present in the thermoplastic composition. Exemplary light stabilizers may include, for example, benzotriazoles (classes), such as 2-(2-hydroxy-5-methylphenyl) benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)-benzotriazole and 2-hydroxy-4-n-octyloxybenzophenone, or a combination including at least one of the aforementioned light stabilizers. Light stabilizers can generally be used in an amount of about 0.1 to about 1.0 parts by weight, based on a total composition of 100 parts by weight, excluding any filler. The thermoplastic composition may also include a plasticizer. For example, a plasticizer may include phthalates, such as dioctyl-4,5-epoxy-hexahydrophthalate, tris-(octyloxycarbonylethyl) isocyanurate, tristearic acid glyceryl, epoxidized soybean oil, or a combination including at least one of the aforementioned plasticizers. Plasticizers are generally used in an amount of about 0.5 to about 3.0 parts by weight, based on a total composition of 100 parts by weight, excluding any filler.

[0101] Ultraviolet (UV) absorbers may also be present in the disclosed thermoplastic compositions. Exemplary UV absorbers may include, for example, hydroxybenzophenones (classes); hydroxybenzotriazoles (classes); hydroxybenzotriazines (classes); cyanoacrylates (classes); oxanilides (classes); benzoxazinones (classes); 2-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)-phenol (CYASORB TM 5411); 2-Hydroxy-4-octyloxybenzophenone (CYASORB TM531); 2-[4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine-2-yl]-5-(octyloxy)-phenol (CYASORB TM 1164); 2,2'-(1,4-phenylene)bis(4H-3,1-benzoxazin-4-one)(CYASORB TM UV-3638); 1,3-bis[(2-cyano-3,3-diphenylacryloyl)oxy]-2,2-bis[[(2-cyano-3,3-diphenylacryloyl)oxy]methyl]propane (UVINUL TM 3030); 2,2'-(1,4-phenylene)bis(4H-3,1-benzoxazin-4-one); 1,3-bis[(2-cyano-3,3-diphenylacryloyl)oxy]-2,2-bis[[(2-cyano-3,3-diphenylacryloyl)oxy]methyl]propane; nano-sized inorganic materials such as titanium oxide, cerium oxide and zinc oxide, all of which have a particle size of less than 100 nanometers; and the like, or a combination comprising at least one of the foregoing UV absorbers. UV absorbers are generally used in an amount of 0.01 to 3.0 parts by weight, based on 100 parts by weight of the total composition, excluding any filler.

[0102] The thermoplastic composition may further include a lubricant. As an example, the lubricant may include, for example, a fatty acid ester, such as an alkyl stearyl ester, such as methyl stearate, etc.; a mixture of methyl stearate with a hydrophilic and hydrophobic surfactant (including polyethylene glycol polymers, polypropylene glycol polymers and copolymers thereof), such as methyl stearate and polyethylene glycol-polypropylene glycol copolymers in a suitable solvent; or a combination comprising at least one of the foregoing lubricants. The lubricant may generally be used in an amount of about 0.1 to about 5 parts by weight, based on 100 parts by weight of the total composition, excluding any filler.

[0103] Anti-drip agents may also be used in the composition, such as fibril-forming or non-fibril-forming fluoropolymers, such as polytetrafluoroethylene (PTFE). The anti-drip agent may be encapsulated by a rigid copolymer such as styrene-acrylonitrile copolymer (SAN). PTFE encapsulated in SAN is referred to as TSAN. In one example, TSAN may comprise 50% by weight of PTFE and 50% by weight of SAN, based on the total weight of the encapsulated fluoropolymer. SAN may comprise, for example, 75% by weight of styrene and 25% by weight of acrylonitrile, based on the total weight of the copolymer. The anti-drip agent (e.g., TSAN) may be used in an amount of 0.1 to 10 parts by weight, based on 100 parts by weight of the total composition, excluding any filler.

[0104] As an example, the disclosed composition may include an impact modifier. The impact modifier may be a chemically reactive impact modifier. By definition, a chemically reactive impact modifier may have at least one reactive group such that when the impact modifier is added to a polymer composition, the impact properties of the composition (expressed as the value of IZOD impact) are improved. In some examples, the chemically reactive impact modifier may be an ethylene copolymer having reactive functional groups selected from, but not limited to, anhydrides, carboxyls, hydroxyls, and epoxy groups.

[0105] In a further aspect of the present disclosure, the composition may include a rubbery impact modifier. The rubbery impact modifier may be a polymeric material that can substantially recover its shape and size after removing the force at room temperature. However, the rubbery impact modifier should generally have a glass transition temperature of less than 0°C. In certain aspects, the glass transition temperature (Tg) may be less than -5°C, -10°C, -15°C, wherein a Tg of less than -30°C generally provides better performance. Representative rubbery impact modifiers may include, for example, functionalized polyolefin ethylene-acrylate terpolymers, such as ethylene-acrylate-maleic anhydride (MAH) or glycidyl methacrylate (GMA). The functionalized rubbery polymer may optionally contain repeating units in its backbone (backbone, main chain), the repeating units being derived from monomers containing anhydride groups, such as maleic anhydride. In another case, the functionalized rubbery polymer may contain anhydride moieties that are grafted onto the polymer in a post-polymerization step.

[0106] Properties and products

[0107] In certain aspects, the disclosed composites may exhibit microwave absorption and shielding properties. A molded article or plate comprising the composite may exhibit a dielectric constant between 5 and 30 and a dissipation loss between 0.5 and 45 measured at frequencies between about 10 and about 120 GHz. At frequencies between about 10 and about 120 GHz, the dissipation factor Df (tanδ,ε" / ε') may be between 0.01 and 2. A plate molded from the disclosed composite may exhibit certain microwave absorption properties. For example, a molded plate having a thickness of about 0.125 inches (3.175 mm) may reflect at least 14% of incident microwave radiation having a frequency of about 75 GHz to 110 GHz. This property may be evident for a molded plate having a thickness between 1 mm and 5 mm. A plate molded from the disclosed composite may exhibit The disclosed composites may exhibit certain attenuation properties. As the carbon filler content increases, the attenuation increases. For example, attenuation values ​​of at least -5 dB / cm to about -150 dB / cm in the K band and attenuation values ​​of -25 dB / cm to about -200 dB / cm in the W band are observed. Panels molded from the disclosed composites may exhibit certain shielding properties. The total shielding may improve as the amount of carbon black increases. For example, shielding effectiveness values ​​of at least 2 dB to about 30 dB in the K band and shielding effectiveness values ​​of at least 10 dB to 60 dB in the W band are observed.

[0108] However, with the increase of carbon black filler in PBT resin, absorption and reflection behave differently. Surprisingly, the maximum microwave absorption is found at about 4 wt % of carbon filler. In some examples, the composite may include about 3 wt % to about 7 wt % of carbon filler, and thus may exhibit an absorbed power percentage of at least 74% when measured in transmission mode when observed at 77 GHz.

[0109] In various aspects, the present disclosure relates to articles comprising the compositions herein. The compositions can be molded into useful shaped articles to form articles by various means such as injection molding, extrusion, rotational molding, blow molding and thermoforming. The compositions can be used to make articles that require materials with good flowability, good impact strength and good dielectric strength. In various aspects, the compositions can also be used for conductive purposes. The advantageous features of the compositions disclosed herein make them suitable for a range of uses.

[0110] Method for preparing the composite

[0111] Aspects of the present disclosure further relate to methods for preparing composites including thermoplastic polymer components. In many aspects, the compositions can be prepared according to various methods. The compositions of the present disclosure can be blended, compounded or otherwise combined with the above-mentioned ingredients by a variety of methods, which involve intimately mixing the materials with any additional additives desired in the formulation. Since melt blending equipment is available in commercial polymer processing facilities, melt processing methods can be used. In various further aspects, the equipment used in such melt processing methods may include, but is not limited to, co-rotating and counter-rotating extruders, single screw extruders, co-kneaders, disc-pack processors, and various other types of extrusion equipment. In a further aspect, the extruder is a twin-screw extruder. In various further aspects, the composition can be processed in an extruder at a temperature of about 180°C to about 350°C, particularly 250°C to 300°C.

[0112] The method may further include processing the composite to provide a plate of desired thickness. The plate may be extruded, injection molded, compression molded or injection-compression molded, and may have a thickness between about 0.5 mm and 6 mm. Other processes may also be applied to thin thermoplastic films, including but not limited to lamination, coextrusion, thermoforming or hot pressing. In such respects, further layers of other materials (e.g., other thermoplastic polymer layers, metal layers, etc.) may be combined with the composite. The present disclosure encompasses various combinations of the elements of the present disclosure, e.g., combinations of the elements of the dependent claims from which the same independent claim is subordinate.

[0113] definition

[0114] It will also be understood that the terms used herein are for the purpose of describing specific aspects only and are not intended to be limiting. As used in the specification and in the claims, the term "comprising" may include embodiments "consisting of" and "consisting essentially of". Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the present disclosure belongs. In this specification and in the appended claims, reference will be made to many of the terms that will be defined herein.

[0115] As used in the specification and the appended claims, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. Thus, for example, reference to a "thermoplastic polymer component" includes a mixture of two or more thermoplastic polymer components. As used herein, the term "combination" includes blends, mixtures, alloys, reaction products, and the like.

[0116] Ranges may be expressed herein as from a value (first value) to another value (second value). When such a range is expressed, the range includes one or both of the first value and the second value in some aspects. Similarly, when a value is expressed as an approximation by using the antecedent "about", it will be understood that the specific value forms another aspect. It will be further understood that the endpoints of each range are significant relative to the other endpoints and are independent of the other endpoints. It is also understood that many values ​​are disclosed herein, and in addition to the value itself, each value is also disclosed herein as "about" the specific value. For example, if the value "10" is disclosed, "about 10" is also disclosed. It is also understood that each unit between two specific units is also disclosed. For example, if 10 and 15 are disclosed, 11, 12, 13 and 14 are also disclosed.

[0117] As used herein, the terms "about" and "at or about" mean that the amount or value in question can be a specified value, approximately the specified value, or about the same as the specified value. As used herein, it is generally understood that, unless otherwise indicated or inferred, nominal values ​​represent ±10% variations. The term is intended to convey that similar values ​​promote equivalent results or effects listed in the claims. That is, it is understood that amounts, dimensions, formulations, parameters, and other quantities and features are not and do not need to be exact, but may be approximate and / or larger or smaller as needed, reflecting tolerances, conversion factors, rounding, measurement errors, etc., as well as other factors known to those skilled in the art. Typically, amounts, dimensions, formulations, parameters, or other quantities or features are "about" or "approximate", whether or not explicitly stated as such. It is understood that, in the case of using "about" before a quantitative value, unless otherwise specifically stated, the parameter also includes the specific quantitative value itself.

[0118] As used herein, the term "optional" or "optionally" means that the subsequently described event or circumstance may or may not occur, and that the description includes instances where the event or circumstance occurs and instances where the event or circumstance does not occur. For example, the phrase "optional additional process" means that the additional process may or may not be included, and that the description includes methods that include and do not include the additional process.

[0119] Disclosed are components to be used to prepare the compositions of the present disclosure and the compositions themselves to be used in the methods disclosed herein. These and other materials are disclosed herein, and it is understood that when the combinations, subsets, interactions, groups, etc. of these materials are disclosed, although it is not possible to explicitly disclose specific reference to each different individual and set combination and arrangement of these compounds, each is specifically considered and described herein. For example, if a specific compound is disclosed and discussed, and many modifications that can be made to many molecules including the compound are discussed, then each combination and arrangement of the compound and possible modifications are specifically considered, unless explicitly indicated to the contrary. Therefore, if a class of molecules A, B and C and a class of molecules D, E and F are disclosed and an example AD of the combined molecule is disclosed, then even if each is not listed separately, each is also considered individually and collectively, meaning that the combination AE, AF, BD, BE, BF, CD, CE and CF are considered to be disclosed. Similarly, any subset or combination of these is also disclosed. Therefore, for example, the subgroups of AE, BF and CE will be considered to be disclosed. This concept applies to all aspects of the application, including but not limited to the steps in the method for preparing and using the compositions of the present disclosure. Thus, if there are a variety of additional steps that can be performed it is understood that each of these additional steps can be performed with any specific aspect or combination of aspects of the methods of the present disclosure.

[0120] References in the specification and the appended claims to parts by weight of a particular element or component in a composition or article represent the weight relationship of the element or component to any other elements or components in the composition or article expressed in parts by weight. Thus, in a compound containing 2 parts by weight of component X and 5 parts by weight of component Y, X and Y are present in a weight ratio of 2:5, and are present in this ratio regardless of whether additional components are present in the compound.

[0121] Unless expressly stated to the contrary, the weight percentage of a component is based on the total weight of the formulation or composition in which the component is included.

[0122] The terms "residue" and "structural unit" used with respect to components of a polymer are synonymous throughout this specification.

[0123] In one aspect, "substantially free" can be less than about 0.5 weight percent (wt.%). In another aspect, substantially free can be less than about 0.1 wt.%. In another aspect, substantially free can be less than about 0.01 wt.%. In yet another aspect, substantially free can be less than about 100 ppm. In yet another aspect, substantially free can refer to amounts below detectable levels, if present.

[0124] As used herein, the terms "weight percent," "weight % (wt%)," and "weight % (wt.%)," which may be used interchangeably unless otherwise indicated, represent the weight percent of a given component based on the total weight of the composition. That is, all wt. % values ​​are based on the total weight of the composition, unless otherwise indicated. It should be understood that the sum of the wt. % values ​​of all components in a disclosed composition or formulation equals 100.

[0125] Unless otherwise stated herein to the contrary, all test standards are the latest standards in effect at the time of filing this application. Each material disclosed herein is commercially available and / or the method for preparing it is known to those skilled in the art. It is understood that the compositions disclosed herein have certain functions. Certain structural requirements for performing the disclosed functions are disclosed herein, and it is understood that there are various structures that can perform the same functions associated with the disclosed structures, and these structures will generally achieve the same results.

[0126] ASPECTS OF THE DISCLOSURE

[0127] The present disclosure relates to and includes at least the following aspects.

[0128] Aspect 1. A composite comprising: about 50 wt % to about 97 wt % of a thermoplastic resin, wherein the thermoplastic resin comprises a polyester; and about 3 wt % to about 15 wt % of a carbon-based filler, wherein the carbon-based filler has a carbon content of about 500 to about 1000 m 2 / g of main surface area, wherein the composite exhibits a dielectric constant ε' between 5 and 30 and a dissipation loss ε" between 0.5 and 45 when measured at a frequency between about 10 and about 120 GHz, wherein a molded sample of the composite exhibits a reflected power percentage of at least 15% when measured in transmission mode when observed at a frequency of about 75 GHz to 110 GHz according to a free space method, and wherein the combined weight percentage values ​​of all components do not exceed 100 weight percent, and all weight percentage values ​​are based on the total weight of the composite.

[0129] Aspect 2. The composite of aspect 1, wherein the polyester comprises a polyalkylene terephthalate polymer.

[0130] Aspect 3. The composite according to any one of aspects 1-2, wherein the polyester comprises polybutylene terephthalate.

[0131] Aspect 4. The composite according to any one of aspects 1-3, wherein the composite has a dissipation factor (Df) of about 0.01 to about 2 when the dissipation factor (Df) is determined as the ratio of ε" and ε' measured in transmission mode.

[0132] Aspect 5. The composite according to any one of aspects 1-4, wherein a 3.175 mm (1 / 8 inch) thick molded plaque comprising the composite absorbs about 60% or more of incident microwave radiation having a frequency of about 75 GHz to 110 GHz.

[0133] Aspect 6. The composite of any of aspects 1-5, wherein a 3.175 mm (1 / 8 inch) thick molded plaque comprising the composite reflects at least 14% of incident microwave radiation having a frequency of about 75 GHz to 110 GHz.

[0134] Aspect 7. The composite of any of Aspects 1-6, wherein a molded plaque comprising the composite exhibits a microwave attenuation of at least about −30 dB / cm in the W band and a total shielding effectiveness of at least about 7 dB in the W band when measured according to a free space method.

[0135] Aspect 8. The composite of any of Aspects 1-7, wherein the composite exhibits a surface resistivity of at least 30 ohms / square when tested according to ASTM D 257.

[0136] Aspect 9. The composite of any of Aspects 1-7, wherein the composite exhibits a volume resistivity of at least 10 ohm·cm when tested according to ASTM D 257.

[0137] Aspect 10. The composite of any of Aspects 1-7, wherein the ratio of the thermoplastic resin to the carbon-based filler is from about 32:1 to about 6:1.

[0138] Aspect 11. The composite of aspects 1-10, wherein the carbon-based filler is present in an amount of 3 wt% to 7 wt%, and wherein the percent absorption measured in transmission mode is at least 74% when observed at a frequency of 77 GHz.

[0139] Aspect 12. The composite of any one of Aspects 1-11, wherein the carbon-based filler comprises carbon fibers, carbon powder, graphite, graphene, carbon flakes, carbon nanotubes, or combinations thereof.

[0140] Aspect 13. The composite of any one of aspects 1-11, wherein the carbon-based filler comprises carbon powder and is free of or substantially free of carbon nanotubes, carbon flakes, or carbon fibers.

[0141] Aspect 14. The composite of any one of Aspects 1-11, wherein the carbon-based filler comprises carbon black powder.

[0142] Aspect 15. The composite of any one of Aspects 1-11, wherein the carbon-based filler comprises carbon black powder, and wherein the carbon black powder has a carbon content of at least 700 m / s when measured according to the BET method.2 / g of surface area.

[0143] Aspect 16. The composite of any one of aspects 1-11, wherein the carbon-based filler has a primary particle size of 10 nm to 50 nm.

[0144] Aspect 17. The composite of any one of Aspects 1-11, wherein the carbon-based filler has a DBP absorption of 80 ml / 100 g to about 500 ml / 100 g.

[0145] Aspect 18. The composite of any one of Aspects 1-15, wherein the composite is free of or substantially free of glass fibers.

[0146] Aspect 19. The composite of any one of Aspects 1-16, further comprising an additive material selected from the group consisting of antioxidants, colorants, de-molding agents, dyes, flow promoters, flow modifiers, light stabilizers, lubricants, release agents, pigments, colorants, quenchers, heat stabilizers, ultraviolet (UV) absorbers, UV reflectors, UV stabilizers, epoxy chain extenders, flame retardants, and combinations thereof.

[0147] Aspect 20. The composite of any one of Aspects 1-17, wherein the composite is a component of an automotive radar sensor.

[0148] Aspect 21. The composite of any one of Aspects 1-18, wherein the composite is a microwave absorbing device or a component thereof.

[0149] Aspect 22. An automatic tracking radar sensor for electromagnetic radiation, comprising a composite comprising: about 50 wt % to about 97 wt % of a thermoplastic resin, wherein the thermoplastic resin comprises a polyalkylene terephthalate; and about 0.05 wt % to about 50 wt % of a carbon-based filler, wherein the composite exhibits a dielectric constant ε' between 5 and 30 and a dissipation loss ε" between 0.5 and 45 when measured at a frequency between about 10 and about 120 GHz, wherein a molded sample of the composite exhibits a reflected power percentage of at least 15% when measured in transmission mode when observed at a frequency of about 75 GHz to 110 GHz according to a free space method, and wherein the combined weight percentage values ​​of all components do not exceed 100 wt %, and all weight percentage values ​​are based on the total weight of the composite.

[0150] Aspect 23. A composite comprising: about 50 wt % to about 97 wt % of a thermoplastic resin, wherein the thermoplastic resin comprises a polyester; and about 3 wt % to about 7 wt % of a carbon-based filler, wherein the carbon-based filler has a carbon content of about 500 to about 1000 m 2 / g of average surface area, wherein the composite exhibits a dielectric constant ε' between 5 and 30 and a dissipation loss ε" between 0.5 and 45 when measured at a frequency between about 10 and about 120 GHz, wherein a molded sample of the composite exhibits an absorbed power percentage of at least 74% when measured in transmission mode when observed at a frequency of about 75 GHz to 110 GHz according to a free space method, and wherein the combined weight percentage values ​​of all components do not exceed 100 weight percent, and all weight percentage values ​​are based on the total weight of the composite.

[0151] Aspect 24. A composite comprising: about 50% to about 97% by weight of a thermoplastic resin, wherein the thermoplastic resin comprises a polyester; about 5% to about 15% by weight of a carbon-based filler, wherein the carbon-based filler has a carbon content of about 500 to about 1000 m 2 / g average surface area; and about 0.01 wt % to about 25 wt % glass fiber filler, wherein when tested according to ASTM D638, the composite exhibits a tensile modulus of less than 9,000 MPa, wherein the composite exhibits a tensile modulus of less than 1.0×10 11 ohm-cm volume resistivity, wherein the composite exhibits a dielectric constant ε' between 5 and 30 and a dissipation loss ε" between 0.5 and 45 when measured at a frequency between about 10 and about 120 GHz, wherein a molded sample of the composite exhibits an absorbed power percentage of at least 55% when measured in transmission mode when observed according to a free space method at a frequency of about 10 GHz to 120 GHz, and wherein the combined weight percentage values ​​of all components do not exceed 100 weight percent, and all weight percentage values ​​are based on the total weight of the composite.

[0152] Example

[0153] The following examples are given to provide a person of ordinary skill in the art with a complete disclosure and description of how to prepare and evaluate the compounds, compositions, articles, devices and / or methods claimed herein, and are intended to be purely exemplary and not intended to limit the present disclosure. Efforts have been made to ensure accuracy with respect to numbers (e.g., amounts, temperatures, etc.), but some errors and deviations should be considered. Unless otherwise stated, parts are parts by weight, temperatures are in ° C or are ambient temperatures, and pressures are at or near atmospheric pressure. Unless otherwise stated, percentages relating to compositions are expressed in weight %.

[0154] There are many variations and combinations of mixing conditions such as component concentrations, extruder design, feed rate, screw speed, temperature, pressure and other mixing ranges and conditions that can be used to optimize the product purity and yield obtained by the described process. Only reasonable and routine experimentation will be required to optimize such process conditions.

[0155] Example I. Comparison of polyetherimide and polycarbonate compositions with PBT resin (W tape)

[0156] Various composite samples were prepared. The formulations are presented in Table 1 ( Figure 1 ). The comparative samples included blends of polycarbonate or polyetherimide resin and carbon black and were designated as CE-1 and CE-2. The inventive samples EX-1 to EX-3 combined blends of polybutylene terephthalate resin and carbon black, wherein the carbon black was Ensaco 350G (CB1) and Ensaco 360G (CB2). Figure 2 The Ensaco TM Comparison between commercially available carbon blacks. As shown, CB1 and CB2 used in this article have a carbon black content greater than 700 m 2 / g of surface area, and the surface area is much larger than the surface area of ​​250G.

[0157] Composite samples were prepared on a 40 mm diameter, co-rotating intermeshing twin screw extruder, where the ingredients of the different formulations were added to the extruder, melted, mixed and pushed out of the extruder through a five-hole die plate. The extruder was operated at a screw speed of 200 rpm, a rate of 45 lbs / hr (0.0225 t / hr) and a torque of about 40% of the maximum torque. The extruder barrel temperature was maintained between about 180-195°C (upstream, feed throat of the extruder) and about 250°C (downstream, die plate of the extruder). The die plate temperature was maintained at about 250°C, and the temperature of the melt leaving the extruder was measured to be about 275°C.

[0158] Mechanical and physical properties are presented in Table 3 (Figure 3).As shown, the inventive PBT samples EX-1 to EX-3 have properties comparable to those of CE-1 and CE-2.

[0159] The surface resistivity and volume resistivity of the comparative samples and the samples of the present invention were observed at room temperature and measured according to ASTM D257 under the following conditions: on a molded plate of 4 inches by 5 inches and 1 / 8 inches thick (10.2 cm by 12.7 cm and 0.32 cm thickness), in a voltage range of 10-100 V, at 50% relative humidity (RH) and 23°C ambient conditions. Table 4 ( Figure 4 ) presents the values ​​observed for CE-1, CE-2, EX-2 and EX-3.

[0160] The values ​​of the complex permittivity (dielectric constant ε' and dissipation losses ε") are also observed according to the free space method. The free space method consists of a vector network analyzer connected to two antennas (transmitting antenna and receiving antenna) to focus microwave energy at or through a material plate. The method can be operated in transmission mode (allowing all three modes of energy transfer, transmission, absorption and reflection) or metal back reflection mode (allowing only absorption and reflection, transmission is suppressed due to the use of a metal plate behind the sample). The method is non-contact and is particularly useful at millimeter wave frequencies. The samples are evaluated in two modes: (a) transmission mode and (b) metal back reflection mode, as shown in Figure 2. Figure 5 Presented in.

[0161] For samples CE-1, CE-2, EX-2 and EX-3, the dielectric constant (real part) was observed at frequencies between 75 and 110 GHz. Two different specimens of each sample were observed. Table 5 (shown in Figure 6 (center) presents the values ​​of the imaginary part ε" and real part ε' of the complex dielectric constant and the dissipation loss tan δ (ε" / ε') of CE-1, CE-2, EX-2 and EX-3 at frequencies of 75 GHz, 92.5 GHz and 110 GHz. For similar types and carbon black loadings, the dielectric constant of the PBT-CB resin of the present invention at high frequencies is approximately twice that of the resins based on PC and PEI.

[0162] The reflection loss in the metal back reflection mode was studied for all frequencies (75 GHz – 110 GHz). All samples had the same thickness (1 / 8 inch). Clearly, the reflection loss is constant with frequency. For CE-1, CE-2, EX-2, and EX-3, Table 6 ( Figure 7 ) presents data on the reflection losses observed in the metal back reflection mode when two plates A and B molded from the same resin are measured at frequencies of 75 GHz, 92.5 GHz and 110 GHz. As shown, for similar carbon black loading (14.5%), the reflection losses of the samples of the present invention at high frequencies are similar to those of the comparative PC and PEI based resins.

[0163] Example II. Comparison of polyetherimide and polycarbonate compositions with PBT resin (K tape)

[0164] The complex dielectric constant was also observed at moderate frequencies in the K band (18–26.5 GHz). The real and imaginary parts of the dielectric constant were observed for CE-1, CE-2, EX-2, and EX-3, where Teflon was used as a control or standard. Samples EX-2 and EX-3 of the present invention were each observed in two sets of samples corresponding to EX-2a, 2b and EX-3a, 3b. The following figures present the real and imaginary parts of the dielectric constant, attenuation (decibels / centimeter, dB / cm), shielding effectiveness (dB), and return loss in metal back reflection mode (d / B): For CE1, Figures 8A-8D ; For CE2, Figures 9A-9D ;For EX-2a, Figures 10A-10D ; For EX-2b, Figures 11A-11D ;For EX-3a, Figures 12A-12D ; and for EX-3b, Figures 13A-13D

[0165] The values ​​of real ε' and imaginary ε" of the complex dielectric constant observed in the PBT compositions of the present invention varied between 18 and 25 and between 24 and 45, respectively, while the same values ​​of the comparative compositions varied between 14 and 18 and between 6 and 8, respectively. The values ​​of attenuation observed in the PBT compositions of the present invention varied between -90 and -150 dB / cm, while the same values ​​of the comparative compositions varied between -30 and -40 dB / cm. The values ​​of shielding effectiveness observed in the PBT compositions of the present invention varied between 35 and 55 dB, while the same values ​​of the comparative compositions varied between 13 and 16 dB. The values ​​of reflection loss measured in metal back reflection mode observed in the PBT compositions of the present invention vary between -2 and -4 dB, while the same values ​​for the comparative compositions vary between -3 and -6 dB. These results show that the higher values ​​of the real ε' and imaginary ε" parts of the complex dielectric constant observed in the PBT compositions of the present invention lead to higher values ​​of attenuation and shielding effectiveness when compared to similar control compositions containing the same carbon black added at similar loadings but containing an amorphous matrix resin (PC or PEI) instead of a semi-crystalline matrix resin (PBT).

[0166] Example III. PBT composites with different carbon blacks in the K band (18-26.5 GHz) and W band (75-110 GHz)

[0167] To further investigate the effect of carbon black, PBT-CB composites were prepared with different amounts of carbon black. That is, 2 wt% (CE3), 4 wt% (EX-4), 6 wt% (EX-5), 8 wt% (EX-6), and 10 wt% (EX-7) were evaluated with EX-2 (14.5%). The formulations are presented in Table 7 ( Fig.14 )middle.

[0168] The dielectric properties were observed at 77 GHz on 3.175 mm (0.125 inch) samples. The values ​​are presented in Table 8 ( Fig.15 As demonstrated, increasing the amount of carbon black increases the value of the dielectric constant. Fig.16A is a graphical representation of the dissipation factor tan δ, which shows that the ε” / ε’ ratio increases with increasing carbon loading. Fig. 16B is a graphical representation of the real and imaginary parts of the complex dielectric constant, each of which increases with increasing carbon black loading, where ε" increases faster than ε' as carbon loading increases. Fig.17 is a graphical representation of the decay constant, which appears to become increasingly negative as the amount of carbon black increases. Fig.18 is a graphical representation of the total shielding effectiveness which similarly follows the trend for increasing carbon black content.

[0169] Fig.19 A graphical representation of the percentage power in transmission mode as a function of the amount of carbon added to the formulation is shown. The sum of absorption, reflection, and transmission at each frequency must reach 100% of the incident MW radiation. As the figure shows, as the carbon black content increases, the transmission through the sample decreases because the material becomes increasingly opaque to microwave radiation. The reflected power increases with carbon black loading because as the amount of carbon increases, the material becomes more conductive, behaving more like a metal than a polymer dielectrically. However, surprisingly, the percentage power absorbed in transmission mode increases until about 4% by weight carbon loading, and begins to decrease after 5 or 7% by weight. Therefore, the carbon loading for maximum (about 76%) microwave absorption is about 4% by weight carbon black. Fig. 20 is a graphical representation of the percent power absorbed in transmission mode and metal back reflection mode. Here, in the case of low transmission (samples with 8, 10 and 14.5 wt. % carbon black), there is almost no difference between the results observed in transmission and metal back reflection modes. When the microwave transmission through the sample is low, the results observed in transmission and metal back reflection modes can be explained in terms of whether the transmission is blocked artificially or naturally. In metal back reflection mode, the transmission is intentionally blocked by inserting a metal plate (almost zero transmission) between the receiving antenna and the test sample. On the other hand, in transmission mode, the transmission through the sample is naturally blocked by the high level of carbon particles present in the sample, which serve to block any passage of microwave energy from the sample to the receiving antenna, in much the same way as the metal plate serves to block penetrating radiation when using the metal back reflection measurement mode.

[0170] Table 9 Fig.21 The volume resistivity and surface resistivity of EX-4 to EX-7, CE3 and EX-2 (14.5 wt % carbon black) are presented in FIG. Fig.22A and 22BGraphs of volume resistivity and surface resistivity, respectively, as a function of carbon loading. Clearly, the percolation threshold is between 4 wt% and 8 wt% carbon black. The dielectric properties of compositions EX-4 to EX-7, CE3, and EX-2 were also observed at medium frequencies (K band: 18-26.5 GHz) and high frequencies (W band: 75-110 GHz).

[0171] Fig.23A and Fig. 23B A graphical representation of the real part ε' of the complex dielectric constant of compositions EX-4 to EX-7 and CE3 when observed at mid-frequency (K-band: 18-26.5 GHz) and high-frequency (W-band: 75-110 GHz) is provided. Fig.24A and 24B A graphical representation of the imaginary part ε" of the complex dielectric constant of compositions EX-4 to EX-7 and CE3 when observed at mid-frequency (K-band: 18-26.5 GHz) and high-frequency (W-band: 75-110 GHz) is provided. Fig.25A and 25B A graphical representation of the return loss in metallic back reflection mode for compositions EX-4 through EX-7 and CE3 when viewed at mid-frequency (K-band: 18-26.5 GHz) and high-frequency (W-band: 75-110 GHz) is provided.

[0172] Fig.26A and Fig.26B A graphical representation of the attenuation constants in decibels per centimeter for compositions EX-4 to EX-7 and CE3 when observed at mid-frequency (K band: 18-26.5 GHz) and high frequency (W band: 75-110 GHz) is provided. These results show that as the carbon black content increases, the attenuation properties of the composition samples increase for both bands studied. With increasing carbon, the attenuation increases, becoming more negative. Fig.27A and Fig.27B The total shielding effectiveness in decibels for compositions EX-4 to EX-7 and CE3 when viewed at mid-frequency (K-band: 18-26.5 GHz) and high frequency (W-band: 75-110 GHz) is provided. Again, as the carbon black content increases, the shielding effectiveness of the composite also increases. Shielding effectiveness describes the combined effects of a material's absorption and reflection. Fig.28A and Fig.28BThe percentage of power absorbed in transmission mode for composites EX-4 to EX-7 and CE3 when observed at medium frequencies (K band: 18-26.5 GHz) and high frequencies (W band: 75-110 GHz) as determined according to the free space method is presented. As mentioned previously, when the amount of carbon black increases, the microwave energy absorbed by the material (measured in transmission mode) also increases, at least up to a certain level, and then decreases as the amount of carbon increases further. This result is observed for most of the frequencies studied, and in particular for measurements carried out in the W band. Fig.29A and 29B These microwave absorption results are provided for the K and W band frequencies when the sample is measured in metal back reflection mode. These results show that in metal back reflection mode, since more of the incident energy is reabsorbed into the sample after reflection from the metal plate, higher levels of absorption (above 80% at some frequencies) can be achieved compared to when the sample is measured in transmission mode (where there is no metal plate to block the transmitted radiation).

[0173] The following figure is a graphical representation of the reflected, transmitted and absorbed percentage power in the transmission mode at frequencies between 75 GHz and 110 GHz: For CE3, Fig.30 ;For EX-4, Fig.31 ;For EX-5, Fig.32 ;For EX-6, Fig.33 ;For EX-7, Fig.34 ;For EX-2, Fig.35 These results show that, when viewed in the W band for frequencies between 75 GHz and 110 GHz, as the carbon black level increases, the material becomes more reflective and less transmissive.

[0174] Example IV. PBT Composite with Carbon Black and Glass Fiber

[0175] The glass fiber containing samples were prepared using a two-shot injection molding process. The two-shot injection molding is a process that combines two materials into one molded part. The first material is injected into the mold and the second material is injected onto the first material, thereby creating a multi-material molded part in only one molding cycle. In a common design, the core plate is mounted to a platen or turntable. The first shot molding is closed onto the core and the plastic is injected, thereby creating the base part. Fig.36 and 37An example of a two-shot molding process from the Gemini Group's "Two-shot Molding Design Guide" (https: / / geminigroup.net / plastics / two-shot-and-injection-molding-tpi / processes / two-shot-multi-shot / ) is provided. Fig.37 In the example above, injection point 1 injects material 1 into cavity 1; injection point 2 injects material 2 into cavity 2. The molded part is then ready for demolding.

[0176] It was noted that it was difficult to achieve a clean break at the gate with all materials prepared, especially CE-4 (01152020-1) described below, when using a two-shot (single-step) injection molding process. Samples EX-8 (#2, 01152020-2) and EX-9 (#3, 01152020-3) broke cleanly on almost every shot, and very little effort was required to make these materials run easily.

[0177] The formulation is presented in Table 10 ( Fig.38 ). For example, formulation 01152020-2 (EX-8) contains 40.93 wt % VALOX 195, 29.07 wt % VALOX 315, 10 wt % Ensaco 360G carbon powder, and 20 wt % JM 718 glass fiber. Formulation 01152020-1 (CE-4) contains the same loading of VALOX 195 (40.93 wt %) and VALOX 315 (29.07 wt %), but contains 4 wt % Ensaco 360G carbon powder and 26 wt % JM 718 glass fiber. Finally, formulation 01152020-3 (EX-9) contains 38.88 wt % of VALOX 195, 27.62 wt % of VALOX 315, 13.5 wt % of Ensaco 360G carbon powder, and 20 wt % of JM 718 glass fiber. As can be calculated from these compositions, the ratio of VALOX 195 / VALOX 315 remains constant in the three formulations and is equal to 1.408. It is expected that the dielectric properties of the resin containing a mixture of two PBTs, 10 wt % of conductive carbon black, and 20 wt % of glass fiber are similar to the dielectric properties of the resin control containing the two same PBTs, 10 wt % of conductive carbon black, and no glass fiber. Tables 11, 12, and 13 ( Fig.39 ) show the steady state shear viscosity of the formulation at a shear rate representative of the injection molding process. Tables 14 and 15 ( Fig.40) provides the mechanical properties as well as the volume and surface resistivities of CE-4, EX-8, and EX-9.

[0178] Additional comparative samples CE-5 and CE-6 were prepared, which included a mixture of two PBT resins and 10 wt % and 14.5 wt % carbon black, but without glass fibers. The formulations are presented in Table 16 ( Fig.41A ), and the corresponding properties are shown in Tables 17 and 18 ( Fig.41B ). The samples were run on a commercial extruder at manufacturing speed and small samples were collected after 15, 30, 45 and 60 minutes. After the process was completed, 150 kg of each formulation was collected. Comparisons between the samples are shown in Tables 19, 20 and 21 ( Fig.42 As shown in comparing the samples without glass fibers to the samples containing glass fibers, the tensile strength increased from 7,502 to 10,847 psi (1.45 times increase), the tensile modulus increased from 443,007 to 1,195,628 psi (2.7 times increase), and the surface / volume resistivity remained fairly constant.

[0179] The dielectric properties of samples CE-5 (average thickness 3.196 mm), EX-8 (average thickness 2.344 mm), and EX-9 (average thickness 2.427 mm) were observed at frequencies between 75 GHz and 110 GHz. Fig.43A and 43B The dielectric constant and loss tangent of CE-5 are presented (respectively). Fig.44A and 44B The S-parameter magnitude (dB) and insertion loss (dB) of CE-5 are presented. Fig.45A and 45B The return loss (dB) and attenuation constant (dB / cm) of CE-5 are presented. Fig.46A and 46B The shielding effectiveness (dB) and metal back reflection loss (dB) of CE-5 are presented. Fig.47A and 47B The percentage power in CE-5 transmission mode and the percentage power in metal back reflection mode are presented (respectively). Fig.48A and Fig.48B The dielectric constant and loss tangent of EX-8 are presented (respectively). Fig.49A and Fig.49B The S-parameter magnitude (dB) and insertion loss (dB) of the EX-8 are presented. Fig.50A and Fig.50B The return loss (dB) and attenuation constant (dB / cm) of the EX-8 are presented. Fig.51A and Fig.51BThe shielding effectiveness (dB) and metal back reflection loss (dB) of EX-8 are presented. Fig.52A and Fig.52B The percentage power in EX-8 transmission mode and the percentage power in metal back reflection mode are presented (respectively). Fig.53A and Fig.53B The dielectric constant and loss tangent of EX-9 are presented (respectively). Fig.54A and Fig.54B The S-parameter magnitude (dB) and insertion loss (dB) of the EX-9 are presented. Fig.55A and Fig.55B The return loss (dB) and attenuation constant (dB / cm) of the EX-9 are presented. Fig.56A and Fig.56B The shielding effectiveness (dB) and metal back reflection loss (dB) of EX-9 are presented. Fig.57A and Fig.57B The percentage power in the transmission mode of EX-9 and the percentage power in the metal back reflection mode are presented (respectively). As expected, the dielectric properties of the resin (EX-8) containing a mixture of two PBT resins, 10 wt% conductive carbon black and 20 wt% glass fiber are similar to the dielectric properties of the resin (CE-5) containing the two PBT resins, 10 wt% conductive carbon black but no glass fiber.

[0180] Thus, as provided herein, the dielectric properties of compositions comprising polymers and conductive carbon fillers depend largely on the type of carbon filler (powder, fiber, nanotube, graphene, graphite, etc.) and the concentration of the carbon-based filler present in the formulation. Polymers containing the same amount of low-structure carbon or high-structure carbon cannot be expected to have the same dielectric properties when measured at frequencies between 75 GHz and 110 GHz in the W band. Surprisingly, it was found that carbon black concentrations in the range of 2-14.5 wt % were the ranges where microwave absorption exhibited a maximum. We found that the percentage of absorbed power measured in transmission mode varied from about 58% at 2 wt % carbon to 76% at 4 wt % carbon, and returned to 58% at 14.5 wt % carbon.

[0181] The above description is intended to be illustrative and not restrictive. For example, the embodiments described above (or one or more aspects thereof) can be used in combination with each other. For example, those of ordinary skill in the art can use other embodiments after reading the above description. An abstract is provided to allow readers to quickly determine the nature of the technical disclosure. The abstract is submitted based on the understanding that it will not be used to interpret or limit the scope or meaning of the claims. In addition, in the above-mentioned specific embodiments, various features can be classified together to streamline the present disclosure. This should not be interpreted as an intention that the disclosed features that are not claimed for protection are essential to any claim. On the contrary, the subject matter of the present invention may be less than all the features of the specific disclosed embodiments. Therefore, the attached claims are thus incorporated into the specific embodiments as examples or embodiments, wherein each claim is independently used as a separate embodiment, and it is expected that such embodiments can be combined with each other in various combinations or arrangements. The scope of the present disclosure should be determined with reference to the attached claims and the full scope of the equivalents given by these claims.

[0182] It will be apparent to those skilled in the art that various modifications and variations may be made in the present disclosure without departing from the scope or spirit of the present disclosure. Other embodiments of the present disclosure will be apparent to those skilled in the art in view of the specification and practice disclosed herein. It is intended that the specification and embodiments are considered to be exemplary only, and the true scope and spirit of the present disclosure are indicated by the appended claims. The patentable scope of the present disclosure is defined by the claims, and may include other examples that occur to those skilled in the art. If these other examples have structural elements that are not different from the literal language of the claims, or if they include equivalent structural elements that are not substantially different from the literal language of the claims, these other examples are intended to fall within the scope of the claims.

Claims

1. A compound comprising: 50 wt % to 97 wt % of a thermoplastic resin, wherein the thermoplastic resin comprises a first polybutylene terephthalate resin having a first viscosity of 0.1 dl / g to 1.4 dl / g and a second polybutylene terephthalate resin having a second viscosity of 0.4 dl / g to 1.4 dl / g, and wherein the first polybutylene terephthalate resin and the second polybutylene terephthalate resin are different resins; and 3 to 15 wt. % of a carbon-based filler, the carbon-based filler comprising a 2 / g BET specific surface area of ​​carbon black powder, wherein the composite exhibits a dielectric constant ε' between 5 and 30 and a dissipation loss ε" between 0.5 and 45, measured at frequencies between 10 and 120 GHz. wherein a 3.175 mm (1 / 8 inch) thick molded plaque comprising the composite absorbs 60% or more of incident microwave radiation having a frequency of 75 GHz to 110 GHz and exhibits a reflected power percentage of at least 15% when measured in transmission mode when observed according to a free space method at a frequency of 75 GHz to 110 GHz, wherein the first viscosity and the second viscosity are different, and The combined weight percentage values ​​of all components do not exceed 100 weight %, and all weight percentage values ​​are based on the total weight of the composite.

2. The composite of claim 1, wherein the composite has a dissipation factor (Df) of 0.01 to 2 when the dissipation factor (Df) is determined as the ratio of ε" and ε' measured in transmission mode.

3. The composite of claim 1, wherein a molded plaque comprising the composite exhibits a microwave attenuation of at least -30 dB / cm in the W band and a total shielding effectiveness of at least 7 dB in the W band when measured according to a free space method.

4. The composite of claim 1, wherein the composite exhibits a surface resistivity of at least 30 ohms / square when tested according to ASTM D 257.

5. The composite of claim 1, wherein the composite exhibits a volume resistivity of at least 10 ohm-cm when tested according to ASTM D 257.

6. The composite of claim 1, wherein the ratio of the thermoplastic resin to the carbon-based filler is from 32:1 to 6:

1.

7. The composite of claim 1, wherein the carbon-based filler is present in an amount of 3 wt% to 7 wt%, and wherein the percent absorption measured in transmission mode when observed at a frequency of 77 GHz is at least 74%.

8. The composite according to any one of claims 1 to 7, wherein the carbon-based filler is present in an amount of 4 to 15 wt%.

9. The composite according to any one of claims 1 to 7, wherein the composite further comprises a glass fiber filler.

10. The composite of any one of claims 1-7, wherein the composite comprises 50 to 97 weight percent of a thermoplastic resin, 4 to 10 weight percent of a carbon-based filler, and 0.01 to 25 weight percent of a glass fiber filler.

11. The composite of any one of claims 1-7, wherein the composite is free or substantially free of carbon nanotubes, carbon flakes or carbon fibers.

12. An automatic tracking radar sensor for electromagnetic radiation, comprising a composite comprising: 50 wt % to 97 wt % of a thermoplastic resin, wherein the thermoplastic resin comprises a first polybutylene terephthalate resin having a first viscosity of 0.1 dl / g to 1.4 dl / g and a second polybutylene terephthalate resin having a second viscosity of 0.4 dl / g to 1.4 dl / g, and wherein the first polybutylene terephthalate resin and the second polybutylene terephthalate resin are different resins; and 3 to 15 wt. % of a carbon-based filler, the carbon-based filler comprising a 2 / g BET specific surface area of ​​carbon black powder, wherein the composite exhibits a dielectric constant ε' between 5 and 30 and a dissipation loss ε" between 0.5 and 45, measured at frequencies between 10 and 120 GHz. wherein a 3.175 mm (1 / 8 inch) thick molded plaque comprising the composite absorbs 60% or more of incident microwave radiation having a frequency of 75 GHz to 110 GHz and exhibits a reflected power percentage of at least 15% when measured in transmission mode when observed according to a free space method at a frequency of 75 GHz to 110 GHz, wherein the first viscosity and the second viscosity are different, and The combined weight percentage values ​​of all components do not exceed 100 weight %, and all weight percentage values ​​are based on the total weight of the composite.

Citation Information

Patent Citations

  • Isosorbide-based polycarbonates, method of making, and articles formed therefrom

    US7786246B2

  • Electromagnetic shielding composite comprising nanotubes

    US20020035170A1

  • Intrinsically conductive thermoplastic composition and compounding processing for making conductive fiber

    US20080139065A1

  • Method for preparing conductive thermoplastic resin compositions

    US5876647A